Exploring student satisfaction and perceived learning in online learning environment - Umi Kalsom, Masrom; Nik Aloesnita, Nik Mohd Alwi (Penerbit Universiti Sains Malaysia, 2025)
The unpredictable conditions caused by COVID-19 have pushed online teaching and learning (OTL) to become an essential teaching and learning medium. COVID-19 have greatly influenced the education system and teaching-learning activities. Delivering online lessons has become an essential and integral element for teaching and learning at various levels, from preschools to tertiary levels. The shift from a traditional teaching approach to online delivery has affected many higher education institutions during the pandemic. Many educational institutions are still struggling to cope with the new norms (Johnson et al., 2020; Mukhtar et al., 2020). In coping with the new norms, higher education institutions have made tremendous efforts to guarantee the effectiveness of online learning programmes. Access, cost and learning effectiveness, and student satisfaction are the essential elements to ensure the quality of online learning programmes (Wang, 2006).